2016
DOI: 10.1021/acs.jctc.6b00588
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo MP2 on Many Graphical Processing Units

Abstract: In the Monte Carlo second-order many-body perturbation (MC-MP2) method, the long sum-of-product matrix expression of the MP2 energy, whose literal evaluation may be poorly scalable, is recast into a single high-dimensional integral of functions of electron pair coordinates, which is evaluated by the scalable method of Monte Carlo integration. The sampling efficiency is further accelerated by the redundant-walker algorithm, which allows a maximal reuse of electron pairs. Here, a multitude of graphical processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…The operation costs of MC-MP2 and MC-MP2-F12 for a given accuracy (relative statistical error) were observed to be O(n 3 ) and O(n 4 ), respectively, where n is the number of orbitals. 116,118 The memory cost is negligible. With the redundant-walker convergence acceleration scheme, 119 the method can easily achieve >90% of the perfect parallel scalability up to thousands of CPUs, and an unprecedented speedup by a factor of tens of thousands (relative to one CPU core) on hundreds of GPUs.…”
Section: Stochastic Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The operation costs of MC-MP2 and MC-MP2-F12 for a given accuracy (relative statistical error) were observed to be O(n 3 ) and O(n 4 ), respectively, where n is the number of orbitals. 116,118 The memory cost is negligible. With the redundant-walker convergence acceleration scheme, 119 the method can easily achieve >90% of the perfect parallel scalability up to thousands of CPUs, and an unprecedented speedup by a factor of tens of thousands (relative to one CPU core) on hundreds of GPUs.…”
Section: Stochastic Algorithmsmentioning
confidence: 99%
“…With the redundant-walker convergence acceleration scheme, 119 the method can easily achieve >90% of the perfect parallel scalability up to thousands of CPUs, and an unprecedented speedup by a factor of tens of thousands (relative to one CPU core) on hundreds of GPUs. 118 These are by virtue of completely eliminating two-electron integral evaluations and transformations, and by foregoing the conventional dense-matrix algorithms in favor of more scalable stochastic ones. Figure 2 is a result of the MC-MP2-F12 calculation for tetrahydrocannabinol using the cc-pVDZ basis set.…”
Section: Stochastic Algorithmsmentioning
confidence: 99%
“…For instance, basic underline functionality needed for quantum chemistry calculations, such as matrix operations and molecular integral evaluation, has been implemented. Many other programs are now ported to GPUs resulting in methods ranging from density functional and coupled cluster to multireference, full configuration interaciton methods and very recently a Monte Carlo MP2 . The RI‐MP2 method was ported as well using a simple rerouting of a single linear algebra routine .…”
Section: Introductionmentioning
confidence: 99%
“…Many other programs are now ported to GPUs resulting in methods ranging from density functional [85,86] and coupled cluster [87,88] to multireference, [89,90] full configuration interaciton methods [91] and very recently a Monte Carlo MP2. [92] The RI-MP2 method was ported as well using a simple rerouting of a single linear algebra routine. [67] The authors reported a 4.3 speedup in single point energy calculations of linear alkanes accomplished by using a single precision routine from the compute unified basic linear algebra subprograms (CUBLAS) library.…”
Section: Introductionmentioning
confidence: 99%
“…On that note, we will start by briefly alluding to the existing literature, whichdespite the use of general-purpose GPUs in natural sciences being a rather recent topic-is rich with work devoted to GPU-accelerated quantum chemistry, concerned with diverse topics ranging from the generation of electron repulsion integrals (ERIs), 11-15 over self-consistent Hartree-Fock (HF), complete active space (CAS), and density functional theory (DFT) methods, [16][17][18][19][20][21][22][23][24] to solvent models, 25,26 force fields, 27 and semi-empirical 28 as well as many-body methods. [29][30][31][32][33][34][35][36][37][38] Adding to this quantum, several program packages are today released with full or partial GPU-enabled features, e.g., Terachem, 39 NWChem, 40 among others.…”
Section: Introductionmentioning
confidence: 99%